Empowering rural communities through social entrepreneurship: a case study from an indigenous Dusun woman in Ranau, Sabah - Mohd Sharif, Siti Nurhayati Khairatun (Kulliyyah of Economics and Management Sciences, 2024)
This case study presents an inspiring journey of Wasinah Kuntagil, an indigenous Dusun woman from Sabah. Facing financial challenges due to her husband's illness, she started producing and selling tuhau floss, a traditional culinary delight from her community. Using a social entrepreneurship model, she not only supplemented her family's income but also provided opportunities for others in her community to earn more. By employing an interview method to collect comprehensive data, this research provides a valuable chance for students to examine the decision-making process of a rural entrepreneur and evaluate the positive effects of her management style on the economy and social well-being of the women in her community.